ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI PEMBAYARAN KLAIM ASURANSI JIWA DALAM MENINGKATKAN PELAYANAN KEPADA NASABAH (STUDI KASUS PADA PT ASURANSI JIWASRAYA PERSERO AREA LHOKSEUMAWE) - Firdaus, Rayyan; Akmal, Nurul (Jurnal Akuntansi dan Keuangan, 2019)
This study was conducted to analyze the application of the Jiwasraya insurance claims payment accounting information system in improving service to customer life insurance claims. The data used in this study were primary data directly through the results of interviews with Jiwasraya Insurance Company employees, and customers. This is a descriptive qualitative study. The results of the study showed that the application of the life insurance claims payment accounting information system in improving service to customers at PT. Jiwasraya Insurance Persero Lhokseumawe area consisted of customers preparing all documents used in filing life insurance claims either died due to death or died due to accidents, following procedures for handling and administering death claims, waiting when checking procedures for recording life insurance claims i.e. by opening a claim payment in LBK in accordance with the account or estimated claim number in accordance with the applicable provisions, waiting for the results of life insurance claim reporting, and waiting for the results of the claim disbursement decision to be approved or rejected.